Comparative study between data warehouse and mediation approaches in information integration of heterogeneous biological data - Beeran Kutty, Suhaili (2009)
In recent years, there are various types of data source in different format available in such field that we call heterogeneous data. This project will focus on heterogeneous biological data which is has diversity of sources data in a form of files and databases. Biological data sources store life sciences information that get from several finding techniques like experiments or computational technologies and the data consists o f various file format such as flat file, XML and pdb file and also cover in different data types such as genome, proteome metabolic pathways and regulatory pathways[1]. It is difficult to manage these several heterogeneity sources and these sources work dependently where biologist or researchers need to access them one by one to complete their tasks and experiments. It is time consuming and because of that, information integration approaches have been introduces where several databases can be made to work together. Three principal approaches of information integration are federation, warehousing and mediation [2] where each of this has their own advantages and disadvantages. Focusing on combining of warehousing and mediation approach that a complementary of advantages and disadvantages of both approaches. Response time of retrieval data in mediation, warehousing and combination of both approaches is subject to be analyses.